EKSPERIMENTASI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER DAN LEARNING CELL PADA ASPEK PENGETAHUAN DAN KETERAMPILAN SISWA DITINJAU DARI KECERDASAN EMOSIONAL PADA MATERI OPERASI ALJABAR KELAS VIII SMP NEGERI DI KABUPATEN PACITAN - Domas, Joko; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objective of this research was to know the effect of the learning models on the learning achievement of knowledge and skill aspects in mathematics viewed from the emotional quotient of the students. The learning models compared were NHT, Learning Cell and classical model with scientific approach. This research used the quasi experimental research method. This population was all of the students in Grade VIII of State Junior Secondary Schools in Pacitan regency. The samples of the research were taken by using the stratified cluster random sampling technique and consisted of 261 students, divided into three groups, namely: 88 students in Experimental Group 1, 86 students in Experimental Group 2, and 87 students in Control Group. The instruments of the research include test of learning achievement of the knowledge aspect, test of learning achievement of the skill aspect, and questionnaire of emotional quotient. The technique of analyze data used the two-way multivariate analysis of variance with unbalanced cells. The results of the research were as follows: (1) the cooperative learning model of the NHT and the Learning Cell types with scientific approach gave a better learning achievement of knowledge and skill aspects than the classical learning model with scientific approach, and the cooperative learning model of the NHT and the Learning Cell types with scientific approach gave the same learning achievement of knowledge and skill aspects; (2) the students with the high emotional quotient had a better learning achievement of knowledge and skill aspects than those with the moderate and low emotional quotient, and the students with the moderate and low emotional quotient had the same learning achievement of knowledge and skill aspects; (3) in each learning model with scientific approach, the students with the high emotional quotient had a better learning achievement of knowledge and skill aspects than those with the moderate and low emotional quotient, and the students with the moderate and low emotional quotient had the same learning achievement of knowledge and skill aspects; (4) in each of the emotional quotient, the cooperative learning model of the NHT and the Learning Cell types with scientific approach gave a better learning achievement of knowledge and skill aspects than the classical model with scientific approach, and the cooperative learning model of the NHT and the Learning Cell types with scientific approach gave the same learning achievement of knowledge and skill aspects.Keywords: NHT, learning cell, classical, scientific approach, emotional quotient, knowledge, skill.